2020
DOI: 10.1177/0731684420956719
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterisation of kenaf/PALF reinforced composite-metal laminates: Effects of hybridisation and weaving architectures

Abstract: Fibre metal laminates are advanced sandwich materials that offer various outstanding properties over conventional metallic alloys and composites. This research study intends to investigate the effects of weaving architectures and stacking configurations on the mechanical properties of fibre metal laminates based on kenaf/pineapple leaf fibre. Fibre metal laminates were fabricated through the hot moulding compression technique. Mechanical tests were performed on the kenaf/pineapple leaf fibre-based fibre metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Various studies on the hybridization of natural fiber with FML have been reported, as listed in Table 6. Woven mat jute fiber Aluminum and copper Epoxy Compression molding [185] Plain woven kenaf and woven E-glass Annealed aluminum PP Hot pressing [186] Plain and twill woven kenaf and PALF Aluminum PP Hot molding compression [187] Vieira et al [182] performed the investigation on composites of sisal fiber-reinforced aluminum laminates (SiRALs) and sisal fiber-reinforced composites (SFRC) on their physical and mechanical properties. Characterizations of the composites showed remarkable enhancements of the tensile, flexural, and impact properties (Figure 11) in SiRAL due to presence of aluminum layers in the composite system.…”
Section: Mechanical Performance Of Hybrid Natural Fiber/synthetic Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…Various studies on the hybridization of natural fiber with FML have been reported, as listed in Table 6. Woven mat jute fiber Aluminum and copper Epoxy Compression molding [185] Plain woven kenaf and woven E-glass Annealed aluminum PP Hot pressing [186] Plain and twill woven kenaf and PALF Aluminum PP Hot molding compression [187] Vieira et al [182] performed the investigation on composites of sisal fiber-reinforced aluminum laminates (SiRALs) and sisal fiber-reinforced composites (SFRC) on their physical and mechanical properties. Characterizations of the composites showed remarkable enhancements of the tensile, flexural, and impact properties (Figure 11) in SiRAL due to presence of aluminum layers in the composite system.…”
Section: Mechanical Performance Of Hybrid Natural Fiber/synthetic Fiber-reinforced Polymer Compositesmentioning
confidence: 99%
“…The parabolic curves in Figure 14(a) indicate that no perforation occurred in any of the samples due to quasi-isotropic orientation in P3SNW composites. But in case of 0°/90° WRM composites, the velocity versus deformation curves revealed that the impactor had pierced without resistance 12,34 as shown in Figure 14(b). From impact test results it is noticed that, under same impact velocity, force, drop height and impactor, energy absorption of composites is varied with fibre orientation which attributed to better impact resistance of material behaviour under sudden impact, besides higher fibre content in SNW composite.
Figure 14.Velocity versus deformation of (a) P3SNW and (b) 0°/90° WRM composites.
…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 lists the metallic fillers used in FR applications. In some polymer composites, the metal and natural fibers such as kenaf [ 65 ], flax [ 66 ], and jute [ 67 ] have been added together with the polymeric resin to enhance the structural and thermal stability. Krishnasamy et al [ 65 ] reported that the addition of aluminum and copper in jute epoxy hybrid composite resulted in the excellent thermal stability, as well as improved in their mechanical strength such as tensile and flexural performance.…”
Section: Introductionmentioning
confidence: 99%
“…In some polymer composites, the metal and natural fibers such as kenaf [ 65 ], flax [ 66 ], and jute [ 67 ] have been added together with the polymeric resin to enhance the structural and thermal stability. Krishnasamy et al [ 65 ] reported that the addition of aluminum and copper in jute epoxy hybrid composite resulted in the excellent thermal stability, as well as improved in their mechanical strength such as tensile and flexural performance. According to El-sabbagh et al [ 68 ], by adding some amount of magnesium hydroxide (Mg(OH) 2 )—about 20–30 wt% to the flax reinforced polypropylene composite improved the onset of decomposition temperature and LOI values.…”
Section: Introductionmentioning
confidence: 99%